THE EFFECT OF PADI HUSK BIOCHAR COMBINATION AND CHICKEN MANURE AGAINST KALE GROWTH AND RESULTS (Brassica oleraceae var. Acephala L.) IN PEATLAND - Noni Sari, Kristina; Ruliyansyah, Agus; Zulfita, Dwi (Jurnal Sains Pertanian Equator, 2019)
Kale plants are a type of green vegetables belonging to Brassica originating from the Eastern Mediterranean or Asia. Kale plants are also dubbed the "The Queen of Greens" and are vegetables that are very well known throughout the world because they have very high nutritional and nutritional content. The aim of this research was determine the best dose of a combination of rice husk biochar and chicken manure on the growth and yield of kale on peat soil. This research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. This research started on November 3, 2018 until February 18, 2019. The design used in this study was a Completely Randomized Design (CRD) consisting of 6 treatments namely: (b1) 3 ton biochar / ha + 15 ton chicken manure / ha , (b2) 6 ton biochar / ha + 15 ton chicken manure / ha, (b3) 9 ton biochar / ha + 15 ton chicken manure / ha, (b4) 3 ton biochar / ha + 30 ton chicken manure / ha, (b5) 6 ton biochar / ha + 30 ton chicken manure / ha, (b6) 9 ton biochar / ha + 30 ton chicken manure / ha. Each treatment was repeated 4 times and consisted of 3 plant samples. Observation variables observed in this study were root volume ), number of leaves (strands), leaf area (), leaf chlorophyll content (spad unit), fresh weight of plants (g), and plant dry weight ( g). Based on the results of research that has been carried out that the combination of rice husk biochar 6 ton / ha and chicken manure 15 ton /ha can increase the growth and yield of the best kale plants on peat soil. Keywords: Biochar Rice Husk, Chicken Manure, Kale